The Effect of Economic Growth and Total Population on Poverty Level in North Sulawesi - Runtunuwu, Prince Charles Heston; Tanjung, Fahmi (Jurusan Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Siliwangi, 2020)
This study aims to test and analyze the effect of economic growth and total population to the poverty level in North Sulawesi. The study was conducted in the districts/cities located in North Sulawesi province with a total of 14 districts/cities. The data taken is after the year of 2008, this due to the district/city is lastly bloomed in 2008.Â The data used in this research is quantitative data. This study uses secondary data and the time series data from the year of 2009 until 2016. Panel data is used as a combination of time series and cross section. Meanwhile the crossed section data is taken from all districts/municipalities in North Sulawesi province which is 14 districts/cities (10 districts and 4 cities) with a total of 98 observations obtained in this study. The data used in this research is secondary data obtained from the Central Bureau of Statistics (BPS) at national level. Inferential statistical methods used in the analysis of research data is Dynamic Panel Data (DPD) considering that the sample size is relatively small. This study examined the effect of exogenous variables i.e. economic growth and total population, while the endogenoue one is poverty level. The result shows that simultaneously, economic growth and total population have a significant effect on poverty level in North Sulawesi.